Essence of creativity : a guide to tackling difficult problems - Kim, Steven H. (OUP E-Books., 1990)
This exploration of creativity has been designed to benefit graduate students and researchers in design (computer science and mechanical engineering) and psychologists interested in the analytical aspects of creativity.